The magic of ordinary days [videorecording (DVD)] - Russell, Keri, 1976-; Ulrich, Skeet; Winningham, Mare; Shields, Brent (Hallmark Hall of Fame (DVD videodiscs), 2005)
Pregnant out of wedlock, an educated young woman is pressured by her father into an arranged marriage with a lonely farmer in this drama set during WWII.